Absence of "Cytokine Storm" in Hospitalized COVID-19 Patients: A Retrospective Cohort Study - Maeghan L. Ciampa; Thomas A. O'Hara; Constance L. Joel; Melinda M. Gleaton; Kirti K. Tiwari; Daniel M. Boudreaux; Balakrishna M. Prasad (MDPI AG, 2021)
Background: A rapidly growing number of publications cite "cytokine storm" as a contributing factor in coronavirus disease 2019 (COVID-19) pathology. However, a few recent reports led to questioning of "cytokine storm" theory in COVID-19. This study's primary goal is to determine if exaggerated cytokine response in the range of a "cytokine storm" develops during the initial weeks of hospitalization in COVID-19 patients. Methods: Five proinflammatory cytokines reported to be involved in "cytokine storm" and elevated in COVID-19 (IL-6, IL-8, TNF-α, MCP-1, and IP-10) were analyzed in COVID-19, influenza (with "cytokine storm": CS), and burn injury patients. The effect of dexamethasone use on cytokine response in COVID-19 was also analyzed. Results: None of the five cytokines in COVID-19 patients reached the lower threshold (95% CI) of the influenza (CS) group at any point during the study period. Furthermore, mean concentrations of all five cytokines in the influenza (CS) group and IL-6, IL-8, TNF-α in the burn group were significantly greater than in COVID-19 patients (p < 0.01). Dexamethasone treatment did not significantly alter the concentrations of any of the cytokines analyzed. Conclusions: Exaggerated cytokine response similar to "cytokine storm" was not observed in COVID-19 patients during two weeks of hospitalization.